1998
DOI: 10.1080/00071669888557
|View full text |Cite
|
Sign up to set email alerts
|

Performance, incidence of metabolic disturbances and endocrine variables of food-restricted male broiler chickens

Abstract: 1. This experiment was carried out to evaluate the productive and physiological consequences of a slight but long term food restriction of male broiler chickens from 2 commercial strains. 2. Cobb-500 and Ross chickens were submitted to a 20% food restriction from 8 to 21 d of age. Strain, food programme and their interactive effects were analysed in terms of consequences upon performance, mortality, incidence of sudden death syndrome (SDS) and ascites syndrome (AS), index of right cardiac hypertrophy and plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 19 publications
2
14
1
Order By: Relevance
“…While T 3 decreased in all restricted treatments, T 4 increased significantly in R hens and there was a marked trend towards increase in QR and 2R hens, all in comparison with the AL hens. These findings are consistent with data from previous studies (Klandorf and Harvey 1985;Newcombe et al 1992;Bruggeman et al 1997;Gonzales et al 1998;Dewil et al 1999). The most detailed study in broiler breeder hens by Bruggeman et al (1997) showed, that during ontogeny (2 -24 weeks) T 3 concentration decreased and T 4 concentration increased in both restricted and ad libitum fed hens.…”
Section: Discussionsupporting
confidence: 82%
“…While T 3 decreased in all restricted treatments, T 4 increased significantly in R hens and there was a marked trend towards increase in QR and 2R hens, all in comparison with the AL hens. These findings are consistent with data from previous studies (Klandorf and Harvey 1985;Newcombe et al 1992;Bruggeman et al 1997;Gonzales et al 1998;Dewil et al 1999). The most detailed study in broiler breeder hens by Bruggeman et al (1997) showed, that during ontogeny (2 -24 weeks) T 3 concentration decreased and T 4 concentration increased in both restricted and ad libitum fed hens.…”
Section: Discussionsupporting
confidence: 82%
“…The level of the reduction of mortality by metabolic diseases seems to depend on the level and duration of the feed restriction program applied (Leeson and Summers, 2001). The results of feed restriction on mortality in our study (3 % including the control group, data not shown) are consistent with those of Lippens et al (2000) and Lee and Leeson (2001) but contrast with Teimouri et al (2005) and Gonzales et al (1998), who reported a higher rate (∼ 4 %). However, all these authors used only mildly restricted rations.…”
Section: Discussioncontrasting
confidence: 40%
“…Gonzales et al (1998) reported that quantitative restriction (20% ad libitum) from 8-21 d were not differences with control in T 3 (1.30 vs 1.32 ng/ml) and T 4 (9.46 vs 8.91 ng /ml) at 42 d of age. In addition, Zhan et al (2007) reported that the concentration of T 3 (1.1 vs 1.0 ng/ml) and T 4 (63.3 vs 65.7 ng/ml) in feed withdrawal for 4 h/d (14:00 to 18:00) from 1-21 d of age were not differences than the control during the period of realimentation from 21-62 d of age.…”
Section: Hormone Thyroid (T 3 and T 4 ) Concentrationsmentioning
confidence: 99%